Keanekaragaman Laba-Laba (Araneae) Di Desa Ubedolumolo I Kecamatan Bajawa Kabupaten Ngada - Limbu, Umbu N; Bao, Antonia P; Enga, Anastasia H. P.; Teftae, Oriensi Y. K. (STKIP HARAPAN BIMA, 2025)
Spiders play an important role in agriculture, plantations, and settlements by preventing pest insects. Efforts to conserve ecosystems are fundamentally a right and an absolute obligation for every generation because an ecosystem harbors a wealth of biodiversity, one of which is spiders. The purpose of the research is to determine the diversity of spider species (Araneae) found in the Ubedolumolo I bamboo forest. The research method used is Explorative Descriptive through observation and documentation at each transect. The transect used is a belt transect combined with a quadrat transect. The data obtained were then analyzed for species diversity, uniformity, and dominance of spiders (Araneae). The results show that the number of spiders obtained was 11 species classified into 5 families, with a total of 924 individual spiders overall. The spider species include Argiope appensa, Argiope versicolor, Macracantha hasselti, Nephila pilipes, Heteropoda venatoria, Tigrosa aspersa, Pardosa milvina, Leucauge tessellata, Leucauge argyra, Tylorida ventralis, and Opadometa fastigata. The spider species diversity index of 2.187452 falls into the moderate index category, the evenness index of 0.912239 falls into the high index category, and the dominance index of 0.138877 falls into the low index category.